LITERATURE REVIEW DETERMINATION OF WORK QUALITY AND WORK PRODUCTIVITY: ANALYSIS OF COMMITMENT AND WORK CULTURE - Dinisari Hafat, Suryana Eka; Hapzi Ali (Dinasti Publisher, 2022)
Relevant research or previous research has the function of strengthening a phenomenon and theory that will discuss a relationship or influence of each variable to be studied, so that relevant research or previous research has a very important role in a recent scientific research or article. The review that will be carried out in this article is about Determination of Work Quality and Work Productivity: Analysis of Commitment and Work Culture, a Human Resource Management Literature Study. The purpose of writing in this article is to form a hypothesis of the influence between variables that will be used in further research. The results of this libraryarisearch are: 1) commitment has an influence on work quality; 2) work culture has an influence on the quality of work; 3) commitment has an influence on work productivity; 4) work culture has an influence on work productivity; and 5) work quality has an influence on work productivity.